Sur le degré topologique et ses applications à quelques problèmes aux limits non-linéaires - Azouzi, Mounira (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
Résumé In this thesis, we have studied some essential properties of the topological degree for compact perturbations of the identity or respect to a Fredholm operator of index zero. This theoretical part occupies the first part of the thesis, which begins with some preliminaries about functional analysis. Next, we presented preminaries about the topological degree of Brouwer and Leray-Schauder, Mawhin's coincidence degree and some fundamental properties and theories related to it. The second part is entirely devoted to the applications of this tool to the resolution of boundary problems associated with nonlinear fractional differential equations at resonance case by using the Mawhin coincidence theory. لقد درسنا في هذه األطروحة بعض الخصائص األساسية للدرجة الطوبولوجية للتذبذبات المتراصة بالنسبة لمؤثر الوحدة أو التى تتعلق بمؤثر فريدهولم ذات الدليل صفر. بداية مع الجزء النظري الذي سنقدم فيه بعض المفاهيم األساسية للتحليل الدالي والتذكير بالدرجة الطوبولوجية لبراور و لوري شودار ثم درجة المصادفة لموان وأهم الخصائص والنظريات المتعلقة بها . الجزء الثاني مخصص بالكامل لتطبيق هذه األداة لحل المشاكل ذات الشروط الحدية المرتبطة بالمعادالت التفاضلية الكسرية الغير الخطية في حالة التجاوب باستخدام نظرية المصادفة لموان.
أطروحة دكتوراه تخصص معادالت تفاضلية وتطبيقاتها في العلوم الدقيقة
Keywords: Topological degree, Fredholm operator, Resonance case Mawhin coincidence theory.; الدرجة الطبولوجية، مؤثر فريدهولم، حالة التجاوب، نظرية المصادفة لموان.